The impact of macroprudential policies on bank competition: Empirical study in Vietnam - Do, Hang Thu; Ta, Huyen Thanh; Pham, Linh Hong (Edelweiss Applied Science and Technology, 2024)
In the banking system, excessively low or high levels of competition can impact the stability of the banking system. This paper examines the impact of macroprudential policies on banking competition in Vietnam. Utilizing data from 29 commercial banks over the period from 2009 to 2023, the authors found a positive relationship between these policy tools and banking competition. This indicates that, in addition to stabilizing the banking system, macroprudential policies targeting banks have improved market conditions, increased competition, and contributed to a healthier banking environment in Vietnam. This finding contributes in the implementation of macroprudential policies in Vietnam, as it highlights the ability to enhance positive impacts while mitigating the negative externalities of these tools.